2013
DOI: 10.1002/jez.b.22496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Chemical, Physical, and Biological Stressors on the Incidence and Types of Abnormalities Observed in Bermuda's Cane Toads (Rhinella marina)

Abstract: The interactive effects of contaminants and ultraviolet light (UV)-exposure on the incidence and types of abnormalities observed were measured in newly metamorphosed cane toads (Rhinella marina) from four Bermuda ponds contaminated with petrochemicals and metals. Abnormalities were compared in toadlets that were field-collected, reared in predator exclusion cages, reared in laboratory microcosms exposed to control media or corresponding pond media, and reared in laboratory microcosms exposed to UV-light and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Although artificial, in the sense of an introduced and invasive population, our study provides evidence of innate behavioral plasticity, and resilience to adverse morphological conditions (with unknown origins), which even native non‐invasive populations face. Unusual cases of blindness have also been observed in other toads (Bacon et al ., ) and snakes (Wharton, ; Bonnet et al ., ) introduced on islands. In these cases, some environmental similarities can be highlighted, such as the indication of a predator‐free environment, and the presence of abundant, sessile or slow‐moving prey.…”
Section: Discussionmentioning
confidence: 99%
“…Although artificial, in the sense of an introduced and invasive population, our study provides evidence of innate behavioral plasticity, and resilience to adverse morphological conditions (with unknown origins), which even native non‐invasive populations face. Unusual cases of blindness have also been observed in other toads (Bacon et al ., ) and snakes (Wharton, ; Bonnet et al ., ) introduced on islands. In these cases, some environmental similarities can be highlighted, such as the indication of a predator‐free environment, and the presence of abundant, sessile or slow‐moving prey.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis revealed that pollution affects amphibians predominantly through increased frequency of abnormalities (Egea-Serrano et al 2012). For example, elevated frequencies of limb deformities have been experimentally linked to metal exposure in the presence of ultraviolet light (Bacon et al 2013). We found a high frequency of deformities in the barren sites, but the incidence was confined to only two ponds and absent in adjacent, connected ponds.…”
Section: Direct and Indirect Effects Of Metal Pollutionmentioning
confidence: 59%
“…For example, elevated frequencies of limb deformities have been experimentally linked to metal exposure in the presence of ultraviolet light (Bacon et al. ). We found a high frequency of deformities in the barren sites, but the incidence was confined to only two ponds and absent in adjacent, connected ponds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations